Male terminalia of Ceraphronoidea: morphological diversity in an otherwise monotonous taxon - Mikó, István; Masner, Lubomir; Johannes, Eva; Yoder, Matthew J; Deans, Andrew R (Insect systematics & evolution, 2013)
The skeletomuscular system of male terminalia in Evaniomorpha (Hymenoptera) is described and the functional morphology of male genitalia is discussed. Confocal laser scanning microscopy is the primary method used for illustrating anatomical phenotypes, and a domain-specific anatomy ontology is employed to more explicitly describe anatomical structures. A comprehensive data set of ceraphronoid male genitalia is analyzed, yielding the first phylogeny of the superfamily. One hundred and one taxa, including three outgroups, are scored for 48 characters. Ceraphronoidea are recovered as sister to the remaining Evaniomorpha in the implied weighting analyses. Numerous character states suggest that Ceraphronoidea is a relatively basal apocritan lineage. Ceraphronoidea, Ceraphronidae, and Megaspilinae are each retrieved as monophyletic in all analyses. Megaspilidae is not recovered as monophyletic. Lagynodinae is monophyletic in the implied weighting analyses with strong support and is a polytomy in the equal weighting analysis. Lagynodinae shares numerous plesiomorphies with both Megaspilinae and Ceraphronidae. Relationships among genera are weakly corroborated. Masner is sister of Ceraphronidae. Trassedia is nested within Ceraphronidae based on the present analysis. Because of this and numerous features shared between it and Ceraphron we transfer Trassedia from Megaspilidae to Ceraphronidae. Dendrocerus forms a single monophyletic clade, with modest support, together with some Conostigmus species. This result challenges the utility of such traditional diagnostic characters as ocellar arrangement and shape of the male flagellomeres. Aphanogmus is monophyletic in the implied weighting, but remains a polytomy with Ceraphron in the equal weighting analysis. Gnathoceraphron is always nested within a well-supported Aphanogmus clade. Cyoceraphron and Elysoceraphron are nested within Ceraphron and Aphanogmus, respectively. The male genitalia prove to be a substantial source of phylogenetically relevant information. Our results indicate that a reclassification of Ceraphronoidea both at the family and generic level is necessary but that more data are required.